Bubble evolution and transport in PEM water electrolysis: Mechanism, impact, and management. (May 2023) - Yuan, Shu; Zhao, Congfan; Cai, Xiyang; An, Lu; Shen, Shuiyun; Yan, Xiaohui; Zhang, Junliang
Abstract: Proton exchange membrane water electrolysis (PEMWE), as a promising technology for hydrogen production from renewable energy sources, has great potential for industrial application. Gas bubbles are known to influence the PEMWE cell performance significantly, but a full picture of bubble behaviors and their impacts on cell performance has been lacking. In this review, we first discuss the most recent advances toward understanding the bubble evolution and transport processes as well as the mechanisms of how bubbles impact the PEMWE. Then the state-of-the-art bubble management methods to mitigate bubble-induced performance losses are summarized. Due to the similarity between PEMWE and anion exchange membrane water electrolysis (AEMWE), we also extend related discussions for AEMWE. Lastly, we present principles of bubble management, followed by an outlook of scientific questions and suggestions for future research priorities.